(untitled) (Research, Society and Development, 2024)
Objective: This study seeks to analyze how digital marketing strategies impact patient acquisition and loyalty in dental clinics, considering the evolution of competition in the sector. Methodology: An exhaustive bibliographic review of scientific articles on successful strategies and practices in dental marketing was carried out. Results: The findings highlight that website optimization, the use of SEO and Google Ads increase the visibility of clinics. Social networks emerge as key tools, facilitating interaction with current and potential patients. Marketing personalization and segmentation allow you to create relevant messages, increasing the conversion of prospects into loyal patients. Online reputation management is also identified as a critical factor in patients’ decisions. Conclusion: Digital marketing has transformed recruitment strategies in dental clinics. By properly identifying and segmenting the target audience, personalizing communications and using advanced digital tools, clinics can stand out in a competitive market, thus achieving greater patient acquisition and loyalty.